Born-digital art: documentation models as a conservation measure - Boogen Ybarra, Amelia (Ge-conservacion, 2017)
This article aims to present a revision of the existing documentation models for the conservation of digital and born-digital art. It has been noted that most recognized projects, including latest ones, adjust to specific cases in order to meet the isolated needs of the born-digital art. However, models fitted to give general answers have not been found. It is imperative to revise documentation models for conservation means, due to soft- and hardware obsolescence. This is an opportunity to unify documentation and conservation aspects, which are not always reflected in them. Differing from traditional conservation procedures, often focused in keeping the work or document in its original condition, born-digital works have to be modified and altered regularly for their accessibility and intelligibility. Hence documentation plays an essential role.